Absent Audiovisual Integration Elicited by Peripheral Stimuli in Parkinson's Disease. (12th April 2018) - Ren, Yanna; Suzuki, Keisuke; Yang, Weiping; Ren, Yanling; Wu, Fengxia; Yang, Jiajia; Takahashi, Satoshi; Ejima, Yoshimichi; Wu, Jinglong; Hirata, Koichi
Abstract : The basal ganglia, which have been shown to be a significant multisensory hub, are disordered in Parkinson's disease (PD). This study was to investigate the audiovisual integration of peripheral stimuli in PD patients with/without sleep disturbances. Thirty-six age-matched normal controls (NC) and 30 PD patients were recruited for an auditory/visual discrimination experiment. The mean response times for each participant were analyzed using repeated measures ANOVA and race model. The results showed that the response to all stimuli was significantly delayed for PD compared to NC (allp < 0.01 ). The response to audiovisual stimuli was significantly faster than that to unimodal stimuli in both NC and PD (p < 0.001 ). Additionally, audiovisual integration was absent in PD; however, it did occur in NC. Further analysis showed that there was no significant audiovisual integration in PD with/without cognitive impairment or in PD with/without sleep disturbances. Furthermore, audiovisual facilitation was not associated with Hoehn and Yahr stage, disease duration, or the presence of sleep disturbances (allp > 0.05 ). The current results showed that audiovisual multisensory integration for peripheral stimuli is absent in PD regardless of sleep disturbances and further suggested the abnormal audiovisual integration might be a potential early manifestation of PD.